1998
DOI: 10.1073/pnas.95.26.15446
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on mammalian Hoxc8 early enhancer sequence reveal a baleen whale-specific deletion of a cis-acting element

Abstract: Variations in regulatory regions of developmental control genes have been implicated in the divergence of axial morphologies. To find potentially significant changes in cis-regulatory regions, we compared nucleotide sequences and activities of mammalian Hoxc8 early enhancers. The nucleotide sequence of the early enhancer region is extremely conserved among mammalian clades, with five previously described cis-acting elements, A-E, being invariant. However, a 4-bp deletion within element C of the Hoxc8 early enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Finally, it should be emphasized that sequence similarity in noncoding DNA only suggests a functional role for conserved motifs. However, we and others have shown that a functional analysis is possible with a transgenic approach (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be emphasized that sequence similarity in noncoding DNA only suggests a functional role for conserved motifs. However, we and others have shown that a functional analysis is possible with a transgenic approach (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the loss of transcription factor binding sites in one location might be compensated by de novo evolution of binding sites in another location, as has been demonstrated for the stripe 2 enhancer of even-skipped gene in Drosophila (44). Notwithstanding these possibilities, several studies have shown that changes in cis-regulatory sequences, ranging from subtle differences to extensive restructuring, can account for the altered expression pattern of Hox genes (6,7,(45)(46)(47). For example, the duplicate fugu HoxA2a and HoxA2b genes show distinct expression patterns in the hindbrain.…”
Section: Pattern Of Cne Evolution In Hox Clusters Of Fugu Human Andmentioning
confidence: 99%
“…Whether separate elements of other dentally expressed genes control expression in di¡erent types of teeth remains to be demonstrated. Analyses of cis-regulatory elements from one species in a related model organism (see, for example, Shashikant et al (1998), for the evolution of the vertebral column) might reveal whether di¡erences in expression relevant to dental pattern are due to di¡erences in cis-or trans-acting factors.…”
Section: Approaches To the Further Study Of Modularity And Dissociatimentioning
confidence: 99%